CHARACTERISTICS AND PRINCIPLES OF RESOURCE-ORIENTED TEACHING - Shtepa, Olena (Journal of Education Culture and Society, 2020)
This article addresses the problem of professional training of future psychologists. It is assumed that it is possible to find an optimal correlation between the acquisition of special knowledge and the formation of personal readiness of psychologists for professional activity. As demonstrated in the article, the character of this correlation depends on the use of a specific method of teaching, and more specifically, the conception of teaching oriented towards forming certain personal qualities. For the efficient education of psychologists it is necessary to make a systemic analysis of expected personal changes in the process and as a result of teaching them. In theory we are realizing an analysis of expected personal changes in the process and the result of teaching them in following modern conceptions of teaching: of programmed teaching, of problem-based teaching, of euristic teaching, of developing teaching, of media-education, of interactive teaching, of active social and psychological teaching, of person-oriented teaching, of experiential teaching. In this paper the author analyzes the main principles of resource-oriented teaching. Resource-oriented teaching creates the ground for the optimal combination of the requirements of professional preparation and personal development of psychology students.